Numerical Simulation and Structural Optimization of Combustion Processes in a 750 t/d Waste Incinerator - Lei Zhang; Fei Yang; Li Xu; Shuhui Zhang; Xiaohan Ren (Energies)
This paper presents a numerical simulation and structural optimization study of the combustion process within the grate and boiler furnace of a 750 t/d waste incineration. The study focuses on adjusting the secondary air velocity, secondary air inclination angle, and the arrangement of secondary air nozzles. These adjustments aim to optimize parameters such as the temperature field, pollutant emission, flow field, particle residence time, and filling degree. The findings demonstrate that high-temperature zones, which lead to slagging problems, are likely to form beneath the front arch. The combustibles inside the furnace are thoroughly burnt, reflecting efficient combustion. The concentration of NOx in the flue gas at the furnace outlet generally ranges between 170 and 200 ppm. Optimal operating conditions are identified as a secondary air inclination angle of 20° with an air velocity of 55 m/s, and an angle of 30° with an air velocity of 55 m/s and 65 m/s, in conjunction with a relative arrangement of the nozzles. Under these conditions, the incineration furnace achieves its best operational state.